Defence Applications of Multi-Agent Systems International Workshop, DAMAS 2005, Utrecht, The Netherlands, July 25, 2005, Revised and Invited Papers - Thompson, Simon G.; Ghanea-Hercock, Robert (Lecture Notes in Artificial Intelligence,, 2006)
Defence applications are subject to some of the world's most demanding requirements for reliability, controllability, security, flexibility, and synchronization. The evolution of defence processes towards network enabled systems and rapid deployment scenarios, is creating an urgent demand for highly adaptive and autonomous information support systems. In particular there are requirements for reduced manpower in support roles, autonomous IT infrastructures, and automated logistics and planning, all of which provide significant scope for an agent-oriented solution set. The workshop addresses the use of agent systems and agent applications applied to defence scenarios in support of these requirements. This book constitutes the thoroughly refereed post-proceedings of the International Workshop on Defence Applications of Multi-Agent Systems, DAMAS 2005, held in Utrecht, The Netherlands in July 2005 as an associated event of AAMAS 2005, the main international conference on autonomous agents and multi-agent systems. The 10 revised full papers presented together with 1 invited article are organized in topical sections on decision support and simulation, unmanned aerial vehicles, as well as on systems and security.